1999
DOI: 10.1097/00000539-199910000-00009
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effectiveness of Cell Salvage to Minimize Perioperative Allogeneic Blood Transfusion in Cardiac and Orthopedic Surgery

Abstract: This meta-analysis of all published randomized trials provides the best current estimate of the effectiveness of cell salvage and is useful in guiding clinical practice. We conclude that cell salvage in orthopedic surgery decreases the proportion of patients requiring allogeneic blood transfusion perioperatively, but postoperative cell salvage is only marginally effective in cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0
9

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 50 publications
0
103
0
9
Order By: Relevance
“…Cell Saver has also been shown to decrease the amount of other blood transfusions in children undergoing acetabuloplasty [12]. A meta-analysis of the literature on the topic of anesthesia examining the effectiveness of Cell Saver found that its use in orthopedic surgery decreased the need for other transfusions [3]. Reitman et al [5] studied Cell Saver use in adult lumbar fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell Saver has also been shown to decrease the amount of other blood transfusions in children undergoing acetabuloplasty [12]. A meta-analysis of the literature on the topic of anesthesia examining the effectiveness of Cell Saver found that its use in orthopedic surgery decreased the need for other transfusions [3]. Reitman et al [5] studied Cell Saver use in adult lumbar fusion surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether use of Cell Saver decreases the need for other transfusions in this patient population. While some studies have found that Cell Saver use decreases the need for other blood transfusion in orthopedic surgery [1][2][3][4], others have found its use to be of little or no benefit [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous reinfusion following arthroplasty is controversial with regard to its effect on postoperative hemoglobin levels and the need for blood transfusion in the perioperative period [2,5,11,13,16,19,20,26,29,34,35]. Nevertheless, autologous reinfusion seems to be safe, as we were unable to find any mention of complications and/or adverse reactions directly related to the reinfusion of autologous blood into a peripheral intravenous line.…”
Section: Discussionmentioning
confidence: 77%
“…The benefits of cell salvage in reducing allogeneic blood transfusion is controversial. A meta-analysis failed to find any significant benefit from cell salvage in cardiac surgery [57] , while other studies demonstrated a significant reduction in blood transfusion with washed salvaged blood [55][56][57][58] . One of the major limitations of washing blood in pediatric surgery is that it is time-consuming during which the blood is unavailable to the patient.…”
Section: Cell-salvage Techniquesmentioning
confidence: 98%